The importance of recovering precious metals from waste electrical and electronic equipment. Issue 1 (February 2021) - Ardelean, M; Ardelean, E; Mihuţ, G; Găianu, O
Abstract: The evolution of electronic equipment in recent decades is experiencing a remarkable development. Due to increasing of consumption and also a very fast replacement rate due mainly to obsolescence, the amount of resulting electrical and electronic waste (WEEE) is increasing. The WEEE term includes all of electrical and electronic equipment starting from mobile phones, computers, video cameras to tv set, washing machines, refrigerators. In other words, all electrical and electronic equipment from a household, electronic equipment from automotive or industrial electronic components. Now in all worldwide it is estimated that WEEE represents about 5% of all municipal solid waste. The recovery process can be taken into account only if the cost of recovery is much lower than the value of the precious metals recovered from this. Regarding to waste disposal restrictions and strict environmental regulations, are needed economically viable and environmentally friendly technologies. The paper presents the results of laboratory experiments on the recovery of precious metals, especially gold, present in various electrical and electronic components. WEEE used in the experiments was used from mobile phones, computer motherboards, computerized microprocessors and various types of gold-plated contacts.